Post baccalaureate reverse transfer students and two-year restrictive access allied health programs - McHugh, Evan J., author; Davies, Tim, advisor; Tochterman, Suzanne, advisor; Brouillette, John, committee member; Morgan, George, committee member (Colorado State University. Libraries, 2003)
This dissertation presents and compares the demographics and pre-admission profiles of post-baccalaureate reverse transfer (PBRT) students who apply to the restricted allied health programs of nursing (ADN), dental hygiene (ADH) and radiological technology (ART) to non-bachelor degree students applying to the same program. In addition, information concerning the impact PBRT students who are accepted into restricted access allied health programs are having on the mission statement of the institution is also presented. Eleven allied health programs (5-nursing, 3-dental hygiene, 3-radiological technology) in the state of Colorado provided grade point averages of prerequisite coursework, pre-entrance exam scores and whether the applicants were accepted or not into the program. The numbers of PBRT students applying to restricted access allied health programs is small and does not seem to be an issue at this time. However, the numbers of PBRT students who apply to these restricted access allied health programs could possibly increase if other factors such as a weak economy come into play. The pre-admission profile of PBRT students and non-bachelor degree students applying to the restricted access allied health programs showed no statistically significant differences in age, grade point average of required prerequisite coursework, or performance on pre-entrance exam except for radiological technology, where PBRT students were significantly older. In three programs, one nursing and two dental hygiene, non-bachelor degree students were seen as being denied access because PBRT students were accepted into the program. However, in comparison of the two groups of students a chi-square analysis of accepted and not accepted PBRT students and non-bachelor degree students shows no statistical difference in PBRT students being accepted as compared to non-bachelor degree students into the eleven restricted access allied health programs. For the selection criteria of the eleven programs studied, the diversity of criteria used was extensive. Findings provided evidence that the programs which have a restricted access type of selection operate on an autonomous design where interviews with the chairs of these programs expressed that they wanted to maintain their autonomy. However, recent state mandates have threatened this autonomous existence for the nursing programs in Colorado and all nursing programs now operate by a first-come, first-served design.
Keywords: community colleges; higher education; school administration; educational administration; community college education